PERBANDINGAN METODE PEJADWALAN PADA PROYEK YANG BERSIFAT LINIER (STUDI KASUS MENGGUNAKAN METODE BAR CHART, NETWORK PLANNING, DAN TIME CHAINAGE DIAGRAM) - Febri Triwibowo; Imron Roni Wijaya; M. Agung Wibowo; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2013)
The implementatation of the construction works especially on linear construction usually have challenge to plan an effective schedule without disruptionand cost efficiency with outreducing the quality. Several methods of  project scheduling includes: Bar Chart, Network Diagram (CPM, PDM), and linear scheduling method (Time Chainage Diagram).The purposes of this study are to find the general scheduling method of project, to compare and to perform simulation of each type of schedule, and to analyze the strengths and weaknesses of each type of schedule. Data of project schedule was collected from 3 linear projects.  Analysis,  elaboration  and  comparison  of existing schedule was performed. Bar Chart is converted into CPM, PDM and Time Chainage Diagram. The results showed that the Bar Chart is still commonly used in construction projects, Network Diagram are proven to be powerful scheduling and suitable  for  complex  projects because it has the reliability in showing the  relationship  among  activities and the critical path of project activities, and  Linear  scheduling method  are  suitable  for  linear project  because  it can  detect  obstacles or conflicts  among  activities.  To  over come weaknesses of eachtype of  schedule, it should be combined  among    types of  schedule. Recommendations for further study are the use of each type of schedule which is suitable with characteristic of projects, and for further more it could be need more study to improvement the feature of time scheduling methods.